(untitled) (World Bulletin of Education and Learning, 2025)
The formation of a vocalist’s repertoire is a key pedagogical and artistic issue in traditional music performance. In Uzbekistan, the practice of maqom singing—particularly within the traditions of Shashmaqom, Ferghana-Tashkent maqoms, and Khorezm maqom cycles—requires a methodologically grounded and culturally informed approach to repertoire selection. This article examines theoretical principles and pedagogical frameworks used to construct the repertoire of maqom vocalists in Uzbekistan. Drawing on ethnomusicological scholarship, oral transmission practices, performance analysis, and contemporary conservatory curricula, the study argues that repertoire formation is not merely a technical process but a systematic procedure rooted in modal theory, poetry, stylistic norms, and socio-cultural context. The research contributes to a broader understanding of how theoretical approaches shape performance identity and sustainability within Uzbekistan’s maqom tradition.